An implementation of the“active-active”data center - Hao FAN (Dianxin kexue)
With the transition of the traditional data center to cloud data center,government and financial industry's information system disaster recovery and backup becomes an important means to ensure services continuity and data availability.Active-active data center can enhance system availability and improve the utilization of equipment,becoming the future trend of data center construction.Active-active data center involves networking,virtualization,storage technology.These related technologies to achieve active-active in the data center were described,and the effectiveness of the technology was verified by the implementation of the governmental data center.